DYALOG: a computer-based measure of conversational performance. - Erber NP (Journal of the Academy of Rehabilitative Audiology, 1998)
Dyalog is computer software developed for measurement of functional communicative performance. During live or videotaped conversation between a client and partner, the clinician simply pushes a button during breakdown and repair. The computer displays a line graph of fluent and non-fluent conversation, and also displays numerical data: duration/proportion of conversation time occupied by breakdown and repair; number of breakdown and repair events; and average time per event. As an outcome measure, Dyalog can be used to demonstrate the benefits of situational change (e.g., reducing noise) or the benefits of longer-term communication therapy. Clinical applications are discussed.